Pemanfaatan Infografis Bagi Pengelola Wisata Alam Pulau Semut - Hanifah Ikhsani; Muhammad Ikhwan; Eno Suwarno (Universitas Negeri Gorontalo, 2024)
Infographics are a popular form of information today. Infographics use a visual concept approach combined with interesting illustrations because they combine data with colorful designs. Based on these advantages, infographics can be developed as an information and promotion medium for a nature tourism area, namely Ant Island Nature Tourism Pekanbaru. This activity aims to create infographics. The service was carried out at the computer lab of the Faculty of Forestry and Science, Lancang Kuning University, from December 2023 to January 2024. Partners are natural tourism managers, totaling five people. The activities carried out include providing materials, practicing the creation of infographics, assisting the community, and evaluating the partners' knowledge and skills. The evaluation results showed that the partners had increased their knowledge about the meaning, benefits, types, and examples, and how to make infographics of nature tourism on Semut Island, Pekanbaru, by 60%. In addition, the partners were also able to make infographics about the nature tourism area of Semut Island, Pekanbaru, in accordance with the knowledge that the partners had received.